Earthquake engineering education plan for low intensity earthquake region - Ramli, Mohd. Zamri; Adnan, Azlan (2004)
Earthquakes are one of nature’s greatest disasters in this world. Basically the effects of earthquake on the man-made structures are the main problems for architects and engineers because the effects that caused extensive loss of life are collapses of bridges, buildings and dams. Therefore, the earthquake effects may not only be considered by countries that have high risk of strong earthquake but also by those that are exposed to low-to-moderate earthquake such as Kuala Lumpur. In the recent years, other countries like United State of America, England and Japan already have their clear implementation plan for raising awareness to their society. Earthquake Engineering Education is one of the main focuses in their plan. Through to this earthquake engineering education plan; at lease the society are located at the low intensity earthquake region has the guidelines to facing seismic impact. This paper introduced the education plan and hopefully it can be one of the platforms for the further discussion on seismic awareness for Malaysian society.